Drone LiDAR Application For 3D City Model - Afradon Aditya Setyawan; Muhammad Iqbal Taftazani; Syamsul Bahri; Erma Dwi Noviana; Maritsa Faridatunnisa (Journal of Applied Geospatial Information, 2022)
The availability of spatial information in 3D in a city that will apply the smart city concept is minimal or even non-existent. This makes the information conveyed less clear and less accurate. 3D map presentation is an indispensable component in the visualization of smart cities. The acquisition of spatial information in 3D can use several methods, one of which is the LiDAR (Light Detection and Ranging) drone. The Drone LiDAR is one of the new technologies in mapping surveys. Initially, LiDAR technology used a manned aircraft and had very large dimensions. Technological developments have made LiDAR portable using drones. Data acquisition was carried out using a multirotor-type Drone LiDAR from microdrones with a flying height of 60 meters above the ground. An area of ​​6 hectares in the Bulaksumur UGM area is the object of research for the 3D city model building. The objects mapped would range from one-story to five-story buildings. The results of data acquisition in the form of a point cloud are then modeled into a 3D building with the micro station software plugin Terra Solid and Terra Model. Modeling is done using automatic and manual methods. The results obtained are in the form of a 3D city model with a LOD 2 level of detail. The amount of vegetation in the mapped area makes the point cloud detail on the front side of the building less dense. However, the accuracy obtained is quite high, ranging from 0,4 to 5,1 cm, making it suitable for making 3D city models with LOD 2 detailed specifications.